2017
DOI: 10.1016/j.immuni.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Proteomics and Phosphoproteomics Profiling Reveals Dynamic Signaling Networks and Bioenergetics Pathways Underlying T Cell Activation

Abstract: SUMMARY The molecular circuits by which antigens activate quiescent T cells remain poorly understood. We combined temporal profiling of the whole proteome and phosphoproteome via multiplexed isobaric labeling proteomics technology, computational pipelines for integrating multi-omics datasets, and functional perturbation to systemically reconstruct regulatory networks underlying T cell activation. T cell receptors activated the T cell proteome and phosphoproteome with discrete kinetics, marked by early dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
350
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(361 citation statements)
references
References 39 publications
10
350
1
Order By: Relevance
“…Whole and phosphoproteome profiling was performed as recently described 34 . CD8α + and CD8α − DCs were sorted from WT spleen as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole and phosphoproteome profiling was performed as recently described 34 . CD8α + and CD8α − DCs were sorted from WT spleen as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed by our in-house JUMP search engine which has been used in the data processing of numerous publications 34 . Briefly, acquired MS/MS raw files were converted into mzXML format and searched by the JUMP algorithm against a composite target/decoy database to estimate FDR.…”
Section: Methodsmentioning
confidence: 99%
“…This is broadly consistent with the observed importance of mTORC1 in CD8 + Teff cell activation and in the differentiation and activation of some Th cell subsets. Proteomic analysis of Raptor-deficient T cells shows that expression of key transcription factors in metabolic reprogramming (MYC, YY1, GABPA, SREBF1) and components of the translational machinery are dependent upon mTORC1 (Tan et al, 2017), highlighting the central role of mTORC1 in anabolic T cell growth. Moreover, in cytotoxic CD8 + T cells, proteomic analyses have shown that rapamycin treatment to inhibit mTORC1 causes a reduction in cell size and protein content associated with changes in abundance (up as well as down) of approximately 10% of the proteome, including reductions in glucose transporters, and enzymes in the glycolysis and cholesterol synthesis metabolic pathways, as well as of the PtdIns(3,4,5)P3 phosphatase PTEN, and key effector proteins such as IFN-γ, perforin granzyme, and TNFα (Hukelmann et al, 2016).…”
Section: Metabolic Sensing By Mtor and Competition For Nutrients Withmentioning
confidence: 99%
“…10,14,15 Although mitochondrial ATP production appears dispensable for effector T-cell proliferation at later time points, 16 OXPHOS is upregulated after T-cell activation and has pivotal roles in the activation and development of effector T cells. 6 A number of mitochondrial pathways are engaged or remodeled early after activation, 17 including mitochondrial ROS to augment nuclear factor of activated T cells activation 18 and one carbon metabolism to support purine and thymidine synthesis. 19,20 Costimulation can contribute to enhanced mitochondrial respiratory functions early after activation.…”
Section: Effector T-cell Metabolismmentioning
confidence: 99%